PEMBERDAYAAN PEREMPUAN DENGAN PELATIHAN PEMBUATAN USAHA BATIK ECO PRINT - Indriyatni, Lies; Yuliati, Yuliati; Firmansyah, Rifqi; Rahmawati, Icha; Saputro, Suryo; Mudzkarroh, Siti; Najikah, Niswatun (STIE Pelita Nusantara, 2025)
This community service aims to be able to provide insight and training on how to utilize the resources in our environment to be more useful. The method used is a lecture and practice of making eco-print batik, so that in addition to gaining knowledge on how to make batik with a stamp system, participants can also practice how to make it. The results obtained from the Abdimas carried out are as follows: 1) Participants became aware that batik can be done not only with canting as usual but also with stamps of various kinds of plants and flowers; 2) batik can be done with various designs according to your own wishes by utilizing various plants around us, 3) The means used to make batik do not have to be in the form of fabric alone but can be directly in a finished form, such as clothes, t-shirts, mukena, and so on; 4) Inspiring to innovate and create more according to their desires and abilities Keywords: Batik Eco Print, inovation dan kreativity